Evaluation of the distribution of dendritic cells in healthy peri-implant mucosa in comparison to that of healthy gingiva: an original research - Bai, Yendluri Durga; Ramesh, Aditi; Kannam, Deepti; Reddy, Jagadish (International Journal of Advances in Medicine, 2020)
Background: Biofilm formation on the implant surface mainly results in peri-implant diseases which are characterized by the inflammatory destruction of the implant supporting tissues. The host response to infection differs between peri-implantitis and periodontitis, but the mechanisms underlying these differences are not clear till date. In the present study, the distribution of dendritic cell sub populations in healthy peri-implant mucosa (HPIM) was compared with healthy mucosa (HM). Methods: A total of 15 nonsmoker subjects were selected for the study. First sample of healthy mucosa was obtained prior to the implant placement (group I) and second sample of peri-implant mucosa was obtained at the time of placement of gingival former (group II). Immunochemistry was used to quantify dendritic cells in the samples. Statistical analysis used Wilcoxon matched paired test was used to compare the distribution of cells in epithelium and lamina propria. Results: Mean number of factors XIIIa DC in epithelium and lamina propria in group I were 30.37±5.42 and 86.93±13.99 and group II were 50.47±7.27 and 124.33±10.27 respectively. Statistically significant difference in the number of cells in epithelium and lamina propria of group I and group II were noted (p=0.001). Conclusions: In the lamina propria of HPIM, a higher number of factors XIIIa+ DC were observed compared to HM.